Effect of fertility preferences in the number of children. Comparison among Peruvian female workers - Enríquez Canto, Yordanis (2018)
Objective: To evaluate fertility preferences on decreasing the number of children by comparing types of employment in Peruvian female workers. Materials and methods: A secondary analysis of the 2014 National Demographic and Family Health Survey (ENDES) was conducted. The study sample consisted of 13,074 female workers of childbearing age who had sexual intercourse in the last 30 days. The dependent variable was the total number of live births. The main independent variables were fertility preferences (ideal number of children and birth spacing preference), age at first marriage, and wealth index. The odds ratio calculation was used for ordinal logistic regression analysis. Results: The average of live births among female employees is lower (1.49) than that among female self-employed (2.44). This situation is associated with decreased fertility: the ideal number of children is from zero to two (Coeff. = -0.38, OR = 0.68, 95 % CI = 0.47-0.99), and birth spacing preference accounts for four years (Coeff. = -0.68, OR = 0.51, 95 % CI = 0.38-0.69). Conclusions: There are differences between fertility preferences in both groups. However, their impact on decreasing fertility is similar. Inequalities regarding the number of children among the groups relate to differences in the effect of direct and indirect determinants that are more emphasized in female employees. Women tend to adjust their reproductive behavior to work life, by giving it priority over the fulfillment of the reproductive ideal.